The impact of Rupiah/USD exchange, on the Indonesian manufacturing sectors in 2005-2016 - I Ketut Shandy Swastika, Wasiaturrahma, (Opción, 2020)
Currently, Indonesia is developing its manufacturing sector. The purpose of this study is to examine and analyze the determinants of manufacturing sector output. Rupiah/USD exchange rate, credit interest, FDI, and import of the manufacturing sector have a significant effect on the output of Indonesia's manufacturing sector. Based on the results of the short-term estimation, it can be concluded that the output of the manufacturing sector in lag 2, credit interest rate in lag 1 and lag 2, FDI lag 1, and imports of manufacturing lag 1 have a significant effect on the output of Indonesia's manufacturing sector.